Reinventing Tasawwuf Values in Indonesian Traditional Games - Muhammad Ikhsan Attaftazani (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2023)
Games are often seen merely as entertainment, overlooking the valuable lessons they contain. However, Indonesian traditional games possess noble national values that can be utilized for religious instruction. Nevertheless, among Islamic scholars, there is an ongoing debate regarding the permissibility of playing games. This research aims to explore the Islamic perspective on games and demonstrate how Indonesian traditional games can teach tasawwuf values, the spiritual dimension of Islam. By doing so, two key questions will be addressed: (1) What is the Islamic viewpoint on games? and (2) How can traditional Indonesian games serve as a platform for teaching Tasawwuf values? The paper will compare various opinions on games from an Islamic standpoint and analyze the Tasawwuf values inherent in Indonesian traditional games. This research uses a qualitative methodology and collects the data through library research. The findings highlight that traditional games encompass Sufism values such as al-Maqāmat (spiritual stations), self-restraint, and self-isolation (khalwā). This study sheds light on the significance of traditional games in fostering spiritual development and enriching religious education. It highlighted the potential of games as a valuable tool for instilling religious values and promoting holistic growth among individuals, particularly within an Islamic framework.